2021
DOI: 10.1002/dad2.12172
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal dysbiosis associates with reduced CSF Aβ42 in cognitively normal elderly

Abstract: Introduction Periodontal disease is a chronic, inflammatory bacterial dysbiosis that is associated with both Alzheimer's disease (AD) and Down syndrome. Methods A total of 48 elderly cognitively normal subjects were evaluated for differences in subgingival periodontal bacteria (assayed by 16S rRNA sequencing) between cerebrospinal fluid (CSF) biomarker groups of amyloid and neurofibrillary pathology. A dysbiotic index (DI) was defined at the genus level as the abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…However, the theory of oral focal infection has not received enough attention and theoretical support. With the advances of microbiome research, the association between oral microbes and a variety of human chronic diseases has been studied, including inflammatory bowel disease, 3 cancers, 4 cardiovascular diseases, 5 Alzheimer’s disease, 6 diabetes, 7 rheumatoid arthritis, 8 and preterm birth 9 (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the theory of oral focal infection has not received enough attention and theoretical support. With the advances of microbiome research, the association between oral microbes and a variety of human chronic diseases has been studied, including inflammatory bowel disease, 3 cancers, 4 cardiovascular diseases, 5 Alzheimer’s disease, 6 diabetes, 7 rheumatoid arthritis, 8 and preterm birth 9 (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory/ dysbiotic environment may facilitate bacterial access to the subarachnoid space through the cribriform plate. Periodontal research also suggests that oral bacteria or inflammatory biproducts can access the brain via both blood and neuronal routes (Riviere et al, 2002) and our studies suggest oral bacteria can induce amyloid pathology (Riviere et al, 2002;Kamer et al, 2015Kamer et al, , 2021. As such, bacterial DNA whose sources could be from the gut and respiratory pathways or proinflammatory cytokines may access the brain via an olfactory route at the nose-brain interface.…”
Section: Nose-brain Interface: Immunologymentioning
confidence: 65%
“…Low levels of sLF may assist oral dysbiosis, which, in turn, may produce long-term infections and a pro-inflammatory response that weakens the blood brain barrier, facilitating colonization of brain tissue by periodontal bacteria [ 61 ] and accelerating neuroinflammation that contribute to AD pathology [ 62 ]. In this vein, previous studies have shown an association between periodontal disease and brain Aβ accumulation in normal aging, suggesting that periodontal inflammation/infection may accelerate brain Aβ deposition [ 63 , 64 ]. Our results complement these findings, suggesting that reductions of sLF relate to increased regional Aβ burden, which may reflect early immunological alterations potentially associated with higher risk of developing AD [ 60 ].…”
Section: Discussionmentioning
confidence: 99%